Demonstration of the monolithic interconnection on CIS solar cells by picosecond laser structuring on 30 by 30 cm2 modules. (24th November 2014) - Heise, Gerhard; Börner, Andreas; Dickmann, Marcel; Englmaier, Marina; Heiss, Andreas; Kemnitzer, Matthias; Konrad, Jan; Moser, Regina; Palm, Jörg; Vogt, Helmut; Huber, Heinz P.
Abstract: In this paper, we present the selective structuring of all three patterns (P1, P2 and P3) of a monolithic interconnection of CIS (Cu(In, Ga)(S, Se)2 ) thin film solar cells by picosecond laser pulses at a wavelength of 1064 nm. We show results for single pulse ablation threshold values and line scribing of molybdenum films on glass (P1), CIS on molybdenum (P2) and zinc oxide on CIS (P3). The purposes of these processes are the p‐type isolation (P1), cell interconnect (P2) and n‐type isolation (P3), which are required for complete cell architecture. The half micron thick molybdenum back electrode can be structured with a process speed of more than 15 m/s at about 15 W average power without detectable residues and damage by direct induced laser ablation from the back side (P1). The CIS layer can be structured selectively down to the molybdenum at process speeds up to 1 m/s at about 15 W average power, due to the precision of direct laser ablation in the ultrashort pulse regime (P2). The ZnO front electrode layer is separated by clean trenches with straight side walls at process speeds of up to 15 m/s at about 10 W average power, as a result of indirect induced laser ablation (P3). A validation of functionality of all processes is demonstrated on CIS solar cell modules (30 × 30 cm 2 ). By replacing one state‐of‐the‐art process by a picosecond laser process at a time, solar efficiencies could be increased for P1 and P2 and stayed on a similar level for P3. After an optimization of the patterning processes in the R&D pilot line of AVANCIS, we achieved a new record efficiency for an all‐laser‐patterned CIS solar module: 14.7% as best value for the aperture area efficiency of a 30 × 30 cm 2 sized CIS module was reached. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : All three patterns (P1, P2 and P3) of a monolithic interconnection of CIS (Cu(In, Ga)(S, Se)2) thin film solar cells can be performed by picosecond laser structuring at 1064 nm. A validation of functionality of all processes is demonstrated on solar cell modules (30 × 30 cm 2 ). By replacing one state‐of‐the‐art pattern by a picosecond laser process at a time, solar efficiencies of 12.7% for P1, 14.0% for P2 and 13.1% for P3 replacement have been achieved.